The Geometry of an Art. The History of Perspective from Alberti to Monge (Kirsti Andersen's Book Review) - João Pedro Xavier (2010)
Book ReviewKirsti AndersenThe Geometry of an Art. The History ofPerspective from Alberti to MongeNew York : Springer, 2007Reviewed by João Pedro Xavier